Child Character Building Through Futsal Extracurriculars at SMPN 249 Jakarta - Aditya Herlambang; Febi Kurniawan; Arya Kusuma Yuda (UNIVERSITAS NEGERI MAKASSAR, 2022)
The purpose of this study was to determine the influence of child character-building through futsal extracurriculars at SMPN 249 Jakarta. This research uses experimental methods, a type of quantitative research while analyzing data using descriptive statistics. The sample in this study was the entire population of 35 futsal extracurricular participants at SMPN 249 Jakarta. This research instrument uses questionnaires for research data collection. Based on the calculation results of SPSS 28, shows that the pretest results in the table resulted in an average of 114.89 obtained also the posttest results from the research data after being given treatment in the table shows that the average obtained of 154.49 shows that the pretest data has smaller calculation results than the posttest calculation results. The data analysis techniques in this study use statistical formulas, including The calculation of the normality test can be seen that the statistical test value on the pretest is 0.951 and the post-test is 0.958. The homogeneity test obtained a significant value of 0.150 because the sig value was 0.150 > 0.05. The result of the t-test of the paired sample test output table is known to be a Sig. (two-sided) value of 0.001 < 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is a difference between the pretest and posttest which means that there is an influence from the formation of children's character through futsal extracurriculars at SMPN 249 Jakarta.